Cross-Cultural Validation of the Short Form of the Physical Self Inventory (PSI-S) - AŞÇI, FEVZİYE HÜLYA (AMER PSYCHOLOGICAL ASSOC, 2018)
The study examined the cross-cultural validity of the short form of the Physical Self-Inventory (PSI-S) among samples of adolescents speaking French, Dutch, Turkish, Italian, and Arab. A total of 4,867 adolescents (1,173 Belgian Flemish, 598 French, 1,222 Italian, 643 Turkish, 646 Kuwaiti, and 585 Tunisian) completed the original PSI-S version, and a revised version including a positively worded reformulation of the 3 negatively worded PSI-S items. The results supported the factor validity and reliability of revised PSI-S version across all cultural groups, and its superiority when compared to the original version. Compared with confirmatory factor analyses, relying on an exploratory structural equation modeling measurement model resulted in superior solution, and in more cleanly differentiated factors. PSI-S responses proved to be fully invariant across cultural groups, and presented no evidence of differential item functioning as a function of age, gender, body mass index (BMI), and sport involvement. However, the results revealed meaningful mean level differences as a function of gender, age, sport involvement, and BMI that were mostly consistent with the results from previous studies.
Keywords: Physical Self Inventory - Short Form; Dutch; Turkish; Arab; Italian; DESCRIPTION QUESTIONNAIRE; BODY-IMAGE; PSYCHOMETRIC PROPERTIES; PERCEPTION PROFILE; MEASUREMENT INVARIANCE; HIERARCHICAL MODEL; FACTORIAL VALIDITY; ESTEEM; GENDER; ADOLESCENCE